LPS-Induced Inflammation Affects Midazolam Clearance in Juvenile Mice in an Age-Dependent Manner - Zheng Y; Ye PP; Zhou Y; Wu SY; Liu XT; Du B; Tang BH; Kan M; Nie AQ; Yin R; Wang M; Hao GX; et al. (Dove Medical Press, 2021)
Yi Zheng,1 Pan-Pan Ye,2 Yue Zhou,1 Su-Ying Wu,3 Xi-Ting Liu,1 Bin Du,1 Bo-Hao Tang,1 Min Kan,1 Ai-Qing Nie,1 Rui Yin,1 Meng Wang,1 Guo-Xiang Hao,1 Lin-Lin Song,2 Xin-Mei Yang,2 Xin Huang,2 Le-Qun Su,2 Wen-Qi Wang,2 John van den Anker,4- 6 Wei Zhao1,2 1Department of Clinical Pharmacy, School of Pharmaceutical Sciences, Cheeloo College of Medicine, Shandong University, Jinan, 250012, People's Republic of China; 2Department of Clinical Pharmacy, The First Affiliated Hospital of Shandong First Medical University & Shandong Provincial Qianfoshan Hospital, Shandong Engineering and Technology Research Center for Pediatric Drug Development, Shandong Medicine and Health Key Laboratory of Clinical Pharmacy, Jinan, 250014, People's Republic of China; 3Shandong University of Traditional Chinese Medicine, Jinan, People's Republic of China; 4Division of Clinical Pharmacology, Children's National Hospital, Washington, DC, USA; 5Departments of Pediatrics, Pharmacology & Physiology, Genomics & Precision Medicine, George Washington University, School of Medicine and Health Sciences, Washington, DC, USA; 6Department of Paediatric Pharmacology and Pharmacometrics, University Children's Hospital Basel, University of Basel, Basel, SwitzerlandCorrespondence: Wei ZhaoDepartment of Clinical Pharmacy, School of Pharmaceutical Sciences, Cheeloo College of Medicine, Shandong University, Jinan, 250012, People's Republic of ChinaEmail zhao4wei2@hotmail.comPurpose: Inflammation has a significant impact on CYP3A activity. We hypothesized that this effect might be age dependent. Our objective was to conduct a population pharmacokinetic study of midazolam in mice at different developmental stages with varying degrees of inflammation to verify our hypothesis.Methods: Different doses (2 and 5 mg/kg) of lipopolysaccharide (LPS) were used to induce different degrees of systemic inflammation in Swiss mice (postnatal age 9- 42 days, n = 220). The CYP3A substrate midazolam was selected as the pharmacological probe to study CYP3A activity. Postnatal age, current body weight, serum amyloid A protein 1 (SAA1) levels and LPS doses were collected as covariates to perform a population pharmacokinetic analysis using NONMEM 7.2.Results: A population pharmacokinetic model of midazolam in juvenile and adult mice was established. Postnatal age and current body weight were the most significant and positive covariates for clearance and volume of distribution. LPS dosage was the most significant and negative covariate for clearance. LPS dosage can significantly reduce the clearance of midazolam by 21.8% and 38.7% with 2 mg/kg and 5 mg/kg, respectively. Moreover, the magnitude of the reduction was higher in mice with advancing postnatal age.Conclusion: Both inflammation and ontogeny have an essential role in CYP3A activity in mice. The effect of LPS-induced systemic inflammation on midazolam clearance in mice is dependent on postnatal age.Keywords: CYP3A activity, ontogeny, inflammation, pharmacokinetic, mice